Teaching History in a Post-pandemic World: The Perceptions of Teachers on Training - Muñoz, Carlos; Torres, Bastián; Martínez, Rosendo; Carrillo, Olga (Frontiers in Education, 2022)
The purposes of the study were (1) to identify the level of knowledge that teachers in training have on globalization and the world health situation in recent years, with the aim of discovering the critical knots that exist; and (2) to understand the perceptions that teachers in training have on the foundations and purposes of history teaching on the current context of globalization and the health situation. The study is part of the project Proyecto FONDECYT Regular No. 1221872 titled El Desarrollo de habilidades de pensamiento histórico para vivir en sociedad. Tensiones, desafíos y propuestas para el sistema escolar chileno (Historical thinking abilities development to live in society. Tensions, challenges, and proposals for the Chilean school system) and part of the project El desarrollo de habilidades, pensamiento histórico de estudiantes de Pedagogía en Historia y Geografía de la Universidad de Concepción: un estudio de caso para la mejora de la formación inicial docente (Skills development, historical thinking of History and Geography teaching students of the Universidad de Concepción: A case study for the improvement of initial teaching training) (UCO-1798). The information was collected through in-depth interviews with 30 teachers in training of both sexes from the last five cohorts. The results show that teachers in training recognize the importance of teaching history in order for people to know their culture and their past, and to commit themselves in the construction of democratic societies. Moreover, and despite the fact that they perceive their university training to be deficient, which is associated with globalization and the pandemic, teachers in training are able to identify elements and characteristics of both phenomena. This enables them to conduct historical analyses that highlight the existence of skills associated with the development of historical thinking.